Mobile health applications to support children with cancer and their families: a scoping review - Kustiningsih Kustiningsih; Dwi Pudjonarko; Anggorowati Anggorowati; Aris Triwiyatno (Universitas Aisyiyah Yogyakarta, 2026)
Children with cancer experience complex symptom burdens while their families face substantial caregiving challenges. Mobile health applications offer potential solutions, yet comprehensive evidence remains limited. We conducted a scoping review using the Arksey & O'Malley framework and reported according to PRISMA-ScR. Six databases PubMed, Embase (Ovid), CINAHL (EBSCO), PsycINFO (Ovid), Cochrane Library, and Web of Science were searched for English-language studies published 2014–2024. Two reviewers independently screened records in Rayyan and charted data with a piloted form..A total of 1,847 records were identified; after screening, 13 studies met inclusion criteria. Apps predominantly targeted pain, symptom monitoring, and caregiver support. System Usability Scale scores ranged 82.3–96.7; real-world adherence was 60–75%. Key facilitators included nurse champions; barriers included workload and technical issues. Evidence for clinical effectiveness remains limited. Mobile health applications demonstrate high usability and feasibility in pediatric oncology settings. Significant gaps exist in long-term effectiveness, sustained engagement, and global applicability. Future research should prioritize rigorous effectiveness evaluations and health equity considerations to optimize support for children with cancer and their families.